Konsep Etika Guru Perspektif Abuya As-Sayyid Muhammad Alwi Al-Maliki di Era Millenial: (Buku Karya KH. Muh. Najih Maimoen Zubair Rembang Jawa Tengah) - arif, muhamad (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2020)
According to the Islamic perspective, a teacher is an educator who has a very noble task. As explained by Al-Ghozali, the teacher has a duty to educate and improve morals (adab) and to provide in-depth knowledge with the aim of increasing faith in Allah. Meanwhile, Ibn Abd al-Barr explained the figure of a teacher as someone who should adorn himself with Islamic manners. So, teachers should improve their ethics (adab). KH. Najih Maimoen Zubair also highlighted the importance of ethics for teachers. So that it has a book entitled the educational character of Abuya Sayyid Alwi Al-Maliki. KH. Najih discussed the educational character of Abuya Sayyid Alwi Al-Maliki in detail. Based on the above background, the researcher is interested in conducting specific research on how the concept of ethics of the perspective of the teacher of Abuya As-Sayyid Muhammad Alwi Al-Maliki and its relevance was presented by KH. Najib Maimoen Zubair in his book entitled Character Education of Abuya As-Sayyid Muhammad Alawi Al-Maliki. This study uses the literature study method, the primary data source is a book by KH. Najih Maimun Zubair, entitled Educational Character Abuya As-Sayyid Muhammad Alawi Al-Maliki and secondary data sources in this study using several supporting sources from various books and articles such as the book written by KH.M. Hasyim Asyari, entitled adabul alim wal muta'alim, the analysis used is content analysis. The conclusion in this study, explains that the ethics of the perspective teacher Abuya As-Sayyid Muhammad Alwi Al-Maliki is divided into two parts. First, the ethics that teachers must have in themselves, include: Getting closer to Allah, having a love for knowledge, having noble character traits, having a noble character and having a character like writing (making works). Second, it is the ethics of teachers to students and the surrounding community, as well as ethics that are embedded in a teacher, it is not enough to stop with him. implementing darmawan, implementing noble character, getting used to loving the faqir and the poor, and teachers are required to be able to implement the nature of love for experts in science. a concept and implementation of teacher ethics that is very relevant to the changing times and the domination of young teachers in the millennial era.